PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER RELIGIUS PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM SISWA KELAS VIII DI SMPN 3 BANJAR MARGO - Muhammad Fadhli Ashshiddiqie; Raisul Umam Ghazali; Pondra Muliawan (STKIP Subang, 2026)
This study aims to analyze the role of Islamic Religious Education (PAI) teachers in shaping the religious character of eighth-grade students at SMP Negeri 3 Banjar Margo, as well as to identify the strategies, supporting factors, and challenges encountered in the PAI learning process. This research is motivated by the declining practice of religious values among junior high school students, such as low discipline in worship and a decreasing attitude of respect toward teachers and parents.The study employed a descriptive qualitative approach, using observation, interviews, and documentation as data collection techniques. The research subjects consisted of the principal, Islamic Religious Education teachers, and eighth-grade students. Data were analyzed through data reduction, data presentation, and conclusion drawing with verification to obtain a comprehensive understanding of the implementation of teachers’ roles in fostering students’ religious character.The results indicate that Islamic Religious Education teachers play a strategic role in developing students’ religious character through several main functions: (1) exemplary behavior (uswah hasanah), (2) habituation of worship and positive morals, (3) providing advice and religious motivation, and (4) managing a spiritually conducive learning environment. Supporting factors include the principal’s support, routine religious programs (such as congregational prayers, Qur’an recitation, and religious activities), and parental involvement. The challenges faced involve students’ inconsistency in worship, the influence of social media, and limited instructional time for PAI.This study concludes that the success of religious character formation is highly influenced by the integration of teachers’ exemplary behavior, a religious school culture, and collaboration between the school and family. Thus, PAI teachers are not only transmitters of religious knowledge but also moral mentors and spiritual role models who directly contribute to nurturing Islamic values within students.